Allergy alert test for p-phenylenediamine-allergic hair dye users - Coenraads, Pieter Jan; Diepgen, Thomas L.; Weisshaar, Elke (Dermatitis, 2018)
Background Contact dermatitis to hair dyes remains a health concern. Regulations in many countries require consumer self-testing for hair dyes, but no standardized procedure exists. - Objective The aim of this study was to develop a self-test protocol for an allergy alert test (AAT) that can elicit a self-noticeable alert signal in p-phenylenediamine (PPD)-allergic consumers. - Methods Simulating consumer use conditions (open application for 45 minutes after mixing with a developer), PPD-positive hair dye-allergic subjects and PPD-negative control subjects were tested on the forearm and behind the ear with experimental products containing 0.05%, 0.25%, 0.75%, and 2% PPD. Reactions were self-evaluated by subjects and independently assessed by dermatologists. - Conclusions The AAT caused a reaction self-noticeable on the forearm in 90.5% (38/42) and behind the ear in 93% (39/42) of the PPD-positive subjects. This was objectified by a dermatological evaluation. The strength of the AAT response and the number of responding subjects increased with increasing PPD concentrations. Allergy alert test responses were also dependent on the reaction strength of the diagnostic patch test to PPD before the study; in subjects with (+++) patch test reactions, 19 of 19 were positive. All 48 control subjects were negative to the AAT. Therefore, the AAT protocol provides a signal indicative of an allergic reaction in PPD-allergic hair dye consumers.
Gesehen am 22.05.2019
DOI fehlerhaft